Manajemen Kepala Sekolah dalam Meningkatkan Profesionalisme Guru Akidah Akhlak di Madrasah Ibtidaiyah Muhammadiyah Kartasura - Irfan, Muhammad; Makruf, Imam (Center of Language and Cultural Studies, 2021)
This study aims to determine describing the management of school Principals, the inhibiting factors that hinder the principal and factors that support the principal on improving the professionalism of Akidah Akhlak teachers at MI Muhammadiyah Kartasura. This study used qualitative research methods. The research was conducted at MI Muhammadiyah Kartasura from September 2020 to March 2021. The subject of this research was the principal. The informants of this research were vice principals, classroom teachers and Akidah Akhlak teachers. Data collection techniques were carried out through observation, interviews and document analysis. While the data analysis technique of the researcher used descriptive qualitative method. The results showed that: (1) Principal management on improving the professionalism of Akidah Akhlak teachers at MI Muhammadiyah Kartasura was carried out through several things including the principal acting as educator, manager, administrator, supervisor, and motivator. Meanwhile, the professionalism of Akidah Akhlak teachers there is quite good, and they always attend various trainings and workshops. (2) The inhibiting factors for the principal are the lack of infrastructure, and the level of parental concern for students. (3) While the supporting factors for school principals in improving the professionalism of Akidah Akhlak teachers are the existence of a good teacher education background and fostering cooperation between teachers.